Analysis of Determinants of Economic Growth - Maryam Sangadji; Seri Suriani; Abdul Basir; Dian Indah Sari; Samuel PD Anantadjaya (Kontigensi : Jurnal Ilmiah Manajemen, 2023)
This study aims to examine the effect of locally-generated revenue, HDI and inflation on economic growth in the city of Semarang and also to test whether locally-generated revenue and HDI mediate the effect of inflation on economic growth in the city of Semarang. The data used in this research is secondary data. The variable of this research consists of inflation as the independent variable. economic growth as the dependent variable and locally-generated revenue, HDI as a mediating variable. The analytical method uses the path analysis method. The results of the analysis show that inflation has a negative effect on locally-generated revenue, HDI and economic growth. locally-generated revenue and HDI have a positive influence on economic growth. locally-generated revenue and HDI are mediating variables proven to be able to mediate the effect of inflation on economic growth in the city of Semarang.